Inhibition of skin fibrosis in systemic sclerosis by botulinum toxin B via the suppression of oxidative stress. Issue 7 (11th April 2021) - Baral, Hritu; Sekiguchi, Akiko; Uchiyama, Akihiko; Nisaa Amalia, Syahla; Yamazaki, Sahori; Inoue, Yuta; Yokoyama, Yoko; Ogino, Sachiko; Torii, Ryoko; Hosoi, Mari; Akai, Ryoko; Iwawaki, Takao; et al.
Abstract: Oxidative stress has been reported to play an important role in the pathogenesis of skin fibrosis in systemic sclerosis (SSc). We previously identified that botulinum toxin (BTX) injection suppresses pressure ulcer formation in a cutaneous ischemia–reperfusion injury mouse model by regulation of oxidative stress. However, the therapeutic possibility of BTX administration for preventing skin fibrosis in SSc is unclear. The objective of this study was to investigate the effect of BTX‐B on skin fibrosis in a murine model of SSc and determine the underlying mechanism. We found that BTX‐B injection significantly reduced dermal thickness and inflammatory cell infiltration in bleomycin‐induced skin fibrosis lesion in mice. We also identified that the oxidative stress signal detected through bioluminescence in OKD48 mice after bleomycin injection in the skin was significantly decreased by BTX‐B. Additionally, mRNA levels of oxidative stress associated factors (NOX2, HO‐1, Trx2) were significantly decreased by BTX‐B. Apoptotic cells in the lesional skin of bleomycin‐treated mice were significantly reduced by BTX‐B. Oxidant‐induced intracellular accumulation of reactive oxygen species in SSc fibroblasts was also inhibited by BTX‐B. In conclusion, BTX‐B might improve bleomycin‐induced skin fibrosis via the suppression of oxidative stress and inflammatory cells in the skin. BTX‐B injection may have a therapeutic effect on skin fibrosis in SSc.